Decipherable classification of glaucoma using deep neural network leveraging XAI - Chayan, Touhidul Islam; Islam, Anita; Tonny, Anika Rahman; Rahman, Eftykhar (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.